Water activity: Its significance and application in food safety and preservation - ΓΕΝΗΠΩΡΓΗΣ ΚΩΝΣΤΑΝΤΙΝΟΣ Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
One of the most important environmental parameters which affect the growth, biochemical activities and death of microorganisms in foods is water activity (aw). By appropriate adjustment of aw in the food system the food scientist can secure its extended preservation and minimize the possibility of a food-borne disease problem. This paper deals with the following subjects with respect to aw: the effect of aw on the growth and the biochemical activities of microorganisms; the parameters which affect the water requirement of microorganisms; the effect of a» on the survival of microorganisms at low and high temperature; the technology of aw adjustment in foods and its food safety implications and finally a discussion of some recent developments, trends and problems in the application of the aw principle in food preservation